Physical Exercise as a Physiological Modulator of Improving Cardiovascular Health in Obese Women - Sugiharto; Merawati, Desiana; Pranoto, Adi; Winarno, Mashuri Eko; Asim; Susanto, Hendra; Taufiq, Ahmad (Physical Education Theory and Methodology, 2023)
The study purpose was to analyze the effective form of physical exercise in improving cardiovascular health in obese individuals. Materials and methods. Twenty-four (24) obese adolescents, aged 20–24 years, who met the criteria were selected as participants. The participants were divided into 3 groups, namely the control, the strength training, and the endurance training, with 8 participants in each group. Strength training was done with Machine Fitness, while endurance training used a Treadmill. Exercise was done with moderate intensity, for 35 minutes, the frequency of exercise was 3x/week, for 1 month. Heart rate and blood pressure, as parameters of heart health, were measured before and after treatment. Data analysis used the One-way ANOVA test with a significance level of 5%. Results. The results showed that there was a significant difference in cardiovascular health between endurance and strength training (p ≤ 0.05). Conclusions. Based on the study results, it was shown that endurance training is a potential physiological modulator to improve cardiovascular health in obese women.